PENGARUH GAYA MENGAJAR DAN FASILITAS PEMBELAJARAN DI SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA DI SMP KRISTEN KANAAN BANJARMASIN (STUDI KASUS SISWA KELAS IX SMP KRISTEN KANAAN BANJARMASIN) - Nico Kosasih (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the effect of teaching styles and learning facilities on student learning motivation at Kanaan Christian Junior High School in Banjarmasin. The study uses a quantitative approach with an associative design. The study population consists of all 65 ninth-grade students, with a saturated sampling technique used for sampling. Data collection was conducted using a Likert scale questionnaire that had been tested for validity and reliability, supported by interviews and documentation. Data analysis was performed using multiple linear regression with the help of SPSS software, through classical assumption tests, t-tests, F-tests, and determination coefficients. The results showed that teaching styles and learning facilities simultaneously had a positive and significant effect on student learning motivation. Partially, teaching styles had a significant effect on student learning motivation, as did learning facilities, which had a more dominant effect. The coefficient of determination value shows that the two independent variables are able to explain 32.1% of the variation in student learning motivation, while the rest is influenced by other factors outside the research model. These findings emphasize the importance of implementing effective teaching styles and providing adequate learning facilities as strategic efforts to increase student learning motivation.